2021
DOI: 10.1108/ijse-05-2020-0323
|View full text |Cite
|
Sign up to set email alerts
|

How financial development and economic growth influence human capital in low-income countries

Abstract: PurposeThis research aims to explain the effect of financial indicators and economic growth on human capital in low-income countries.Design/methodology/approachWe gathered balanced panel data from 1980 to 2016 over a sample of 12 low-income countries categorized by World Development Indicators. The data stationary properties were analyzed by unit root test while the existence of a long-run relationship among the variables was confirmed by cointegration test. We performed Hausman test to differentiate between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 62 publications
(63 reference statements)
1
8
0
2
Order By: Relevance
“…Negara maju mendorong iklim dan meningkatkan sumber daya investasi untuk mempengaruhi peningkatan kesejahteraan masyarakat baik secara langsung maupun tidak langsung. Sebaliknya, pada studi empiris yang dilakukan oleh (Ali et al, 2021), negara dengan tingkat pendapatan yang rendah atau negara berkembang, masyarakat berharap adanya transisi ekonomi yang sehat yang dapat meningkatkan keterampilan (skills) dan standar hidup. Hubungan antara pembangunan finansial dan pertumbuhan ekonomi telah mendapat perhatian dari para pakar ekonomi sejak awal abad ke-19.…”
Section: Pendahuluanunclassified
“…Negara maju mendorong iklim dan meningkatkan sumber daya investasi untuk mempengaruhi peningkatan kesejahteraan masyarakat baik secara langsung maupun tidak langsung. Sebaliknya, pada studi empiris yang dilakukan oleh (Ali et al, 2021), negara dengan tingkat pendapatan yang rendah atau negara berkembang, masyarakat berharap adanya transisi ekonomi yang sehat yang dapat meningkatkan keterampilan (skills) dan standar hidup. Hubungan antara pembangunan finansial dan pertumbuhan ekonomi telah mendapat perhatian dari para pakar ekonomi sejak awal abad ke-19.…”
Section: Pendahuluanunclassified
“…Ketika negaranegara beralih menuju ekonomi yang berbasis pengetahuan, maka keberadaan sumber daya manusia yang sangat terampil menjadi semakin penting (Rosendo Silva et al, 2018). Sudah banyak penelitian yang menyoroti Human Capital sebagai penentu utama pertumbuhan ekonomi (Ali et al, 2021;Anetor, 2020;Apergis et al, 2022;Duan et al, 2022;Ibrahim, 2018;Neeliah & Seetanah, 2016;Sehrawat & Giri, 2017;Tahir et al, 2020;Tandrayen Ragoobur & Narsoo, 2022). Namun pada kondisi saat ini peran dari health capital secara intens menjadi fokus penelitian dari akademisi (Isreal Akingba et al, 2018).…”
Section: Pendahuluanunclassified
“…Therefore, economic development is significantly associated with the entrepreneurship ecosystem and entrepreneurial skills of people in a country. Previous studies have reported a positive impact of entrepreneurship ecosystem on economic development [ [1] , [2] , [3] , [4] , [5] , [6] ]. The growth of new firms, start-ups and businesses achieve sustainability in long-term in an entrepreneurship ecosystem [ 7 ].…”
Section: Introductionmentioning
confidence: 99%